Sensorial characterization of tamarindo nectars (Tamarindus indica L.) sweetened with xylitol (Research, Society and Development, 2021)
This work aimed to develop sensorial evaluation of the ideal formulation of tamarind nectar sweetened with xylitol. Tamarind fruits from farms in the region of Araguari, Minas Gerais, Brazil, processed and evaluated according to the physical-chemical parameters provided for in the legislation. From the pulp, nectars formulations with different concentrations of tamarind pulp were prepared: 20% (T20), 22% (T22), 24% (T24) and 26% (T26) and then physical-chemical, and sensory analyses (Ideal dilution) were performed. Subsequently, formulations of nectars were prepared with ideal proportion of pulp, with different concentrations of xylitol: 11% (T11), 12% (T12) and 13% (T13) and then performed physicochemical and sensorial analyses (Ideal sweetness). The physicochemical results from pulp and nectars were consistent with the identity and quality standards of pulp and juice of tamarind, with the exception of the results of total acidity of the nectars, since there is no standard of identity and quality for nectar of tamarind, which can may explain these differences. 106 consumers carried out the sensory test of ideal dilution and they indicated samples T24 and T26 as ideal in terms of dilution. In the sensory test of ideal sweetness, applied to 101 consumers, they indicated that the control (12% sugar) and T13 formulations were ideal. The ideal formulation of tamarind nectar consisted of 24% pulp and 13% xylitol.